PRAKTIK MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR KEPEMILIKAN KELUARGA DI INDONESIA - Yuli Dias Pratama, (2022)
This research aims to analyze the effect of family share ownership, dividend policy and firm size on earnings management in the Manufacturing Industry in Indonesia. The research methodology uses a case study quantitative method with a research sample of 46 family-owned manufacturing companies listed on the IDX during the 2017-2019 period. The data analysis technique used is regression with moderating. This research was processed with Eviews and Microsoft Excel. The results of this study indicate that the variable Family Ownership (X1) Dividend Policy (X2) Company Size (X3) has a significant effect on earnings management (Y) while the Firm Value variable is not able to moderate the relationship between Family Ownership and Company Size on Earnings Management.